Pengaruh Frekuensi Pemberian MOL Kohe Kambing dan Macam Pupuk Kandang terhadap Pertumbuhan dan Hasil Lactuca sativa L. serta Perkembangan Mikroorganisme Tanah - diyan nivita; Djuhari Djuhari; Istirochah Pujiwati (AGRONISMA, 2022)
Lettuce (Lactuca sativa L.) is one of the horticultural products that has good prospects and commercial value, but in reality lettuce production is still experiencing a decline in production. One of the factors that reduce lettuce production is the lack of soil fertility. This study aims to determine the interaction of the frequency of administration of Indigenous Microorganisms (IM) goat manure and the type of manure on the growth and yield of L. sativa and the development of microorganisms. The experiment was designed with a Randomized Block Design (RAK). Factor I is the frequency of giving goat Â IM with 4 levels, namely: F1 = 1 time, F2 = 2 times, F3 = 3 times, F4 = 4 times. Factor II is the type of manure, namely: P1 = chicken manure, P2 = goat manure, P3 = cow manure. The best growth response for use chicken manure, goat manure and cow manure is with a frequency of 4 times. While the effect of the best performance of each type of manure is with a frequency of 3 times. The highest number of fungal populations in the soil after application of IM goats was chicken manure at a frequency of 4 times, goat manure at a frequency of 2 times, and cow manure at a frequency of 4 times. Â Keywords : Local Microorganisms, Goat Manure, Frequency, Lactuca sativaÂ